Awareness and Practices of Non-Pharmacological Approaches for Management of Hypertension in a Geriatric Population - Debalina Sahoo; Harshida Gosai; Ujjwal Sahoo; J. M. Harsoda (International Journal of Medical Students, 2014)
Background: There is an increase in the prevalence of hypertension all over the world, including India. Hypertension can be initially managed with non-pharmacological measures. This study aims to assess the knowledge of non-pharmacological measures to control hypertension and its application in a geriatric hypertensive population.